Association of depressive symptoms and quality of life in Pakistani youth (15–24 years) with polycystic ovarian syndrome: a web-based analytical cross-sectional study - Peerwani, Ghazal; Rozi, Shafquat; Lakhdir, Maryam Pyar Ali; Zuberi, Nadeem; Asad, Nargis (Frontiers in Global Women's Health, 2023)
Introduction Polycystic ovarian syndrome (PCOS) is associated with impaired quality of life (QOL) of individuals, predominantly in youth, who are most vulnerable to its impact. Psychological morbidity could be one of the factors influencing QOL. The study investigated the association between depressive symptoms and QOL in Pakistani youth (15–24 years) with PCOS and determined other factors associated with QOL. Methods We conducted an analytical-cross-sectional survey on 213 single Pakistani females aged 15–24 years recruited via a web-based approach. Depression and QOL were assessed through Center-of-Epidemiological-Studies-Depression tool and Polycystic-ovarian-syndrome-quality-of-life-scale. Multiple-linear-regression was used to determine factors associated with QOL, and adjusted regression-coefficients along with a 95% confidence interval were reported. Results The mean QOL score: 2.9 ± 1.1. The domain of obesity had the lowest mean score (2.5 ± 1.6) whereas domain of hirsutism had the highest (3.2 ± 1.9). 172/213 (80%) participants were screened positive for depressive symptoms. Participants with depressive symptoms reported reduced mean QOL scores than respondents with no such symptoms (2.8 ± 1.0 vs. 3.4 ± 1.3, p < 0.001). No differences were found in overall QOL and individual domains between participants 15–19 years (n = 36, 17%) and participants >19–24 years (n = 177, 83%) (2.9 ± 1.1 vs. 2.9 ± 1.1) (p > 0.05). We found a significant interaction between depressive symptoms and PCOS duration, indicating that the estimated mean overall QOL score decreases by 25.1 (−36.6, −13.6) for every year increase in PCOS duration among participants screened positive for depressive symptoms. Furthermore, for those respondents who had family history of PCOS and were not satisfied with their healthcare provider treating PCOS, the estimated mean QOL score was 17.47 (−26.1, −8.8) lower than participants who had no family history of PCOS and were satisfied with their healthcare provider. Other factors associated with reduced quality of life included societal pressure to improve appearance affected by PCOS, parental criticism related to PCOS, education, socioeconomic status, working status and BMI. Conclusion Depressive symptoms with increasing duration of PCOS were significantly associated with reduced QOL. Therefore, to improve the overall QOL of PCOS youth, screening and timely addressing of psychological morbidities should be considered.